THE LANGUAGE OF THE VEPRINAC LAW (1507) - Boris Kuzmić (Fluminensia: Journal for Philological Research, 2001)
In this article, the author analyzes the language of the Veprinac Law, a Croatian glagolitic legal text from the beginning of the 16th century. The linguistic description of the Veprinac Law contains a break-down of the text into its phonological, morphological, and syntactic elements, giving special attention to the similarities and differences between the languages contained in the original (although it's copy of the older original) and the copies of the Veprinac Law. The author also deals with the problem of access to the linguistic structure between the copy of Anton Cora (the second half of the 18th century) and the second one of Jakov Volčić (the second half of the 19th century).